PEAK: Python-based framework for heterogeneous agent communities - Bruno Ribeiro; David Dias; Luis Gomes; Zita Vale (SoftwareX)
Python-based framework for heterogeneous agent communities (PEAK) is a multi-agent system development framework aiming at facilitating the interoperability of agents from different environments and their interactions and exchange of knowledge. With PEAK, it is possible to develop from simple agent systems to more complex ones where hundreds of agents, or even thousands, interact with each other to fulfil their purpose. PEAK has contributed to the validation of solutions, published articles and advanced training sessions in different research fields such as energy systems and federated learning. The idea is that, in the future, it will continue to contribute to the enrichment of scientific knowledge in more fields of application.